Clinical significance of umbilical cord abnormalities: an observational study - Thangappah, Radha B. P.; Karnal, C. Suhashini; Ravichandran, Monika R.; Sowparnika, Alagu Sakthi; Sundaravadivelu, Pavithra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: The well being of a foetus depends on the uncompromised placental function and normal blood flow through the umbilical vessels. If there are umbilical cord abnormalities, it can lead to perinatal complications. The aim of the study was to analyse the prevalence of umbilical cord abnormalities and to study the relationship between the cord abnormalities and intrapartum complications. Methods: This was a prospective observational study conducted at a tertiary care hospital, Chennai, from September 2020 to August 2021. Four hundred mothers who met the inclusion and exclusion criteria were included in the study. At the time of delivery, umbilical cord , intrapartum and neonatal details were noted. The association between the cord length and parameters such as nuchal coiling, FHR changes, mode of delivery, APGAR at birth and NICU admissions were analysed and the statistical significance was derived. Results: The mean cord length was 57.44±20.11 cms. 65% had normal cord length, 15% had short cords and 20% of babies had long cords. Nuchal coiling was seen in 31.75%, cord prolapse in 0.75% and true knot in 1% of cases. Cases with long cords were associated with statistically significant increase in the incidence of nuchal cords, multiple cords, FHR abnormalities, operative interventions and birth asphyxia. The presence of short cord was not associated with significant adverse maternal and perinatal outcome. Conclusions: This study showed that 35% of all deliveries were complicated by abnormal cord length and other cord complications. It is important to document these findings in the event of antenatal or intrapartum complications.